Reader’s Responses of the Colonized Land in Heart of Darkness by Joseph Conrad - Bedihardjo, Sonya Suciati; Ferdinal, Ferdinal (Linguistika Kultura, 2022)
This study discusses colonialism in Africa in Joseph Conrad's Heart of Darkness. It aims to study readers' responses regarding colonialism in the novella. The research uses a reader's response approach applying David Bleich's theory and the postcolonial theory of literary criticism of Edward Said. The methods of collecting data include spreading questionnaires to local officials and library research. The investigation also uses thematic analysis, which identifies, analyzes, and interprets patterns of the data collected from the respondents. This research reveals that everyone has their own opinion and broad view of colonialism. In the readers' responses to Heart of Darkness, the readers show that they are against colonialism and judge this work as a work that describes colonialism.